PENGARUH LATIHAN GRIP PASSING GAME DAN HEAD RETRUN TERHADAP KEMAMPUAN PASSING CONTROLING PADA PEMAIN 11-12 SSB KUANG SUMBAWA BARAT TAHUN 2022 - Soemardiawan; Susi Yundarwati (TEACHING AND LEARNING JOURNAL OF MANDALIKA (TEACHER) e- ISSN 2721-9666, 2023)
Regarding the focus of this research problem, there is shooting at the football club at the 2022 Space Princess Player Nina, finding that there is still a lack of accuracy, the ability to shoot a lot because when playing the goal always misses to the left and right side, and many balls stray upwards so researchers are very motivated to do research on shooting. Research purpose To Find Out whether or not the Influence of Shoot On Goal With Opening Slalom (Passing Combination) And Shooting Squence (Getting Open) Exercises Increased Football Shooting Results In Space Princess Nina Players in 2022. The research design is to use One group pretest-posttest design. In this study, the population did not use samples, but the entire population was used as a research sample, namely the entire Nina Space Princess Player of 2022, amounting to 20 people. So this study is a population study research. So this study is a population study research. Based on the data obtained, from the results of field trials and discussion of research results it can be concluded that: There is a comparison of numbers that show the results of the initial test and the final test is progressing, in the Shoot On Goal With Opening Slalom (Passing Combination) group the output results using SPSS 17, That the average value of the result before being given a spin shooting exercise is 78.00 and after being treated with the Shoot On Goal With Opening Slalom (Passing Combination) exercise 108.50 means that the average value of football shooting is increased, Based on the output results using SPSS 17 that the average value of the results before being given shooting Squence (Getting Open) practice is 90.00 and after being treated with a target game practice of 120.50 means that the average value of shooting football there is an increase.